2000
DOI: 10.1902/annals.2000.5.1.119
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Bone Thickness on Facial Marginal Bone Response: Stage 1 Placement Through Stage 2 Uncovering

Abstract: Significantly greater amounts of facial bone loss were associated with implants that failed to integrate. As the bone thickness approached 1.8 to 2 mm, bone loss decreased significantly and some evidence of bone gain was seen. There was no statistically or clinically significant difference in bone response between HA-coated and non-HA-coated implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
368
4
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 453 publications
(420 citation statements)
references
References 13 publications
(9 reference statements)
25
368
4
4
Order By: Relevance
“…Spray et al [32], with a study conducted on the analysis of peri-implant bone values, mea-sured over 3,061 implants and have come to the same conclusion as well. With a vestibular cortical bone thickness greater than 1.8 mm, there is a reduced buccal/palatal thickness, compared to other sites with a thinner cortical bone.…”
Section: Vertical and Horizontal Bone Resorption Following Immediate mentioning
confidence: 61%
See 1 more Smart Citation
“…Spray et al [32], with a study conducted on the analysis of peri-implant bone values, mea-sured over 3,061 implants and have come to the same conclusion as well. With a vestibular cortical bone thickness greater than 1.8 mm, there is a reduced buccal/palatal thickness, compared to other sites with a thinner cortical bone.…”
Section: Vertical and Horizontal Bone Resorption Following Immediate mentioning
confidence: 61%
“…From a statistical point of view, it can be said that 1.8 mm is the critical thickness of the cortical bone, below which the operator should expect greater crestal bone resorption [32].…”
Section: Discussionmentioning
confidence: 99%
“…Additional factors are loss secondary to aggression such as mucoperiosteal flap raising, second-stage surgery for exposing the screw, and colonization by bacteria belonging to the oral flora at the coronal bone and implant junction (17,19). Other authors have also studied crestal bone loss and its relationship to the facial bone thickness of the patient (20). In numerical terms, bone loss in two-stage implantsupported restorations is estimated to be 1.5-2mm below the implant-abutment junction, exposing one or two threads after one year supporting a prosthetic restoration.…”
Section: Influence Upon Bone Crestal Levelmentioning
confidence: 99%
“…In numerical terms, bone loss in two-stage implantsupported restorations is estimated to be 1.5-2mm below the implant-abutment junction, exposing one or two threads after one year supporting a prosthetic restoration. In general, this exposure of the implant body is not regarded as a sign of failure (20). However, in the studies on platform switching involving a follow-up period of 4-169 months, the reported bone loss varies between 0.05-1.4 mm (Table 1) (21).…”
Section: Influence Upon Bone Crestal Levelmentioning
confidence: 99%
“…The present case report showed that careful surgical and restorative interdisciplinary planning, along with the inclusion of the laboratory technician in decision-making and excellent motivation of the patient, resulted in a highly functional and aesthetic case as well as a satisfied patient. 7,8 Fig. 7 A PFM crown cementation…”
Section: Resultsmentioning
confidence: 99%